Epidydimo-orchitis and anorectal malformations: when and in whom? - Zaccara, A.; Ragozzino, S.; Iacobelli, B. D.; Rivosecchi, F.; Capitanucci, M. L.; Mosiello, G.; Silveri, M.; De Gennaro, M.; Bagolan, P. (Pediatric surgery international, 2015)
Purpose Epididymo-orchitis (EO) is infrequently reported in anorectal malformation (ARM) cases. Therefore, it is difficult to assess its risk factors. Methods A total of 110 male patients who were operated on for ARM at the same Institution over a period of 13 years were contacted. Association was assessed between EO and the following: spinal dysraphism (SD), symptomatic VUR (VUR), and bowel management (BM) requiring enemas. The data were analyzed with the Chi-square test. Results A total of 89 patients were contacted. Ten cases of EO were found, and all occurred in patients with recto-urethral (RU) fistula after reconstruction. The patients’ age at first episode ranged between 4 and 11 years. RU fistula patients experiencing EO (Group A, 10 patients) were compared with those without EO (Group B, 33 patients). VUR occurred in 9/10 cases in Group A and in 13/33 cases in group B (Chi-square 7.8658, p = 0.005038). SD was present in 4/10 cases in group A and in 13/33 cases in Group B (Chi-square 0.0434, p = 0.83491). A total of 8/10 cases in Group A and 12/33 cases in Group B were on BM (Chi-square 5.87, p = 0.0015). Conclusions EO occurs in approximately in 20 % of male cases with ARM, and recto-urinary communication and should be considered the primary diagnosis in the presence of testicular pain. This could avoid unnecessary surgical exploration, and the family should be counseled about this subject